2017
DOI: 10.1002/cctc.201700647
|View full text |Cite
|
Sign up to set email alerts
|

A Mesoporous Cobalt Aluminate Spinel Catalyst for Nonoxidative Propane Dehydrogenation

Abstract: A mesoporous CoAl2O4 spinel (Co‐Al) is synthesized by a one‐step evaporation‐induced self‐assembly (EISA) method. N2 physisorption and TEM are used to demonstrate the presence of mesopores within the Co‐Al material. The spinel crystal structure of Co‐Al, in which Co occupies tetrahedral (Td) sites, is confirmed by using XRD and UV/Vis spectroscopy. In nonoxidative propane dehydrogenation at 550 °C, a propane conversion of approximately 8 % is observed for Co‐Al with a >80 % propylene selectivity, which corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 59 publications
(25 reference statements)
1
46
0
Order By: Relevance
“…The large space of the CoAl 2 O 4 aerogels was occupied by air leads to a lightweight thermal material, which has the potential to thermal insulation. Due to the abundant availability of active catalytic sites of aluminum and cobalt in the oxide composites, the CoAl 2 O 4 aerogels may be a promising catalyst support for various oxidation and reduction reactions [8]. High surface area and large porosity can easily access secondary components to the aerogel networks to accelerate the reaction performance of magnetic CoAl 2 O 4 -based nanocomposites [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large space of the CoAl 2 O 4 aerogels was occupied by air leads to a lightweight thermal material, which has the potential to thermal insulation. Due to the abundant availability of active catalytic sites of aluminum and cobalt in the oxide composites, the CoAl 2 O 4 aerogels may be a promising catalyst support for various oxidation and reduction reactions [8]. High surface area and large porosity can easily access secondary components to the aerogel networks to accelerate the reaction performance of magnetic CoAl 2 O 4 -based nanocomposites [6].…”
Section: Resultsmentioning
confidence: 99%
“…Cobalt aluminates (CoAl 2 O 4 ) is an important ceramic of the normal spinel aluminate family with aluminum in octahedral sites and cobalt in tetrahedral ones [6]. Porous CoAl 2 O 4 nanomaterial is used as a blue pigment component for preparing colorful magnetic ceramics [7] and catalyst supports [8]. The crystallinity, nanoscale, and porosity of alumina are the most critical structured features to determine its reaction performance.…”
Section: Introductionmentioning
confidence: 99%
“…reported that single‐site Co 2+ /SiO 2 exhibits selectivity >95 % at 550 °C and >90 % at 650 °C with stable activity over 24 h in the selective propane dehydrogenation. On the other hand, mesoporous CoAl 2 O 4 spinel showed higher conversion and selectivity at 600 °C owing to the well‐dispersed Co 2+ in the alumina matrix, which revealed the non‐redox type nature of cobalt coordinated with alumina as an active phase for propane dehydrogenation [13c] . Meanwhile, Sun et al [18] .…”
Section: Introductionmentioning
confidence: 99%
“…However, this catalyst suffers from deactivation due to coke deposition and metal attrition, which requires frequent regeneration of the catalyst. [7] Sun et al, also studied the effect of different cobalt loading on alumina and found that 5 % loading of cobalt led to the formation of Co + 2 in the tetrahedral geometry and the higher percentage of cobalt loading led to cracking reaction. Indeed, this catalyst showed promising activity, but suffers from thermal sintering of the alumina support and possess environmental concern due to the presence of Cr (VI).…”
Section: Introductionmentioning
confidence: 99%
“…This was also supported using EXAFS study under reducing atmosphere and reaction condition. [7] Sun et al, also studied the effect of different cobalt loading on alumina and found that 5 % loading of cobalt led to the formation of Co + 2 in the tetrahedral geometry and the higher percentage of cobalt loading led to cracking reaction. [8] Indeed the addition of sulfate group reduces the reduction of CoO to metallic cobalt and also enhances CÀ H bond activation.…”
Section: Introductionmentioning
confidence: 99%